Formulasi Krim dari Ekstrak Kulit Batang Kemiri (Aleurites molucca ( L.) Willd ) dan Uji Aktivitas Antibakteri - kamal, sefrianita; dkk, Sara Surya (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
CreamÂ  is one of the pharmaceutical preparations that used topically forÂ  treatment of skin diseases. Candlenut bark has compounds that have inhibitory activities as antibacterial. In this research, a cream formulation was made from the ethanolic extract of candlenut bark. Candlenut bark extract cream has antibacterial activity against Staphylococcus aureus. Evaluation of cream such as organoleptic, adhesion, homogeneity and obtained good results.